quick math question; exponenets?
(Pf) x (Vf)^x = (Pi) x (Vi)^x
I need to solve for Vi
I came up with
Vi = ((Pf) + ( Vf^x) - (Pi)) / (e^x)
can anyone confirm?
- 1 decade agoFavorite Answer
Take the log of both sides of the equation, separate out (Vi), then exponentiate:
(Pf) (Vf)^x = (Pi) (Vi)^x
log(Pf) + xlog(Vf) = log(Pi) + xlog(Vi)
xlog(Vi) = log(Pf) + xlog(Vf) - log(Pi)
log(Vi) = (log(Pf) + xlog(Vf) - log(Pi))/x
(Vi) = exp[(log(Pf) + xlog(Vf) - log(Pi))/x]
(Vi) = [(Pf) + (Vf)^x - (Pi)]/(e^x)
- 1 decade ago
p cancels as does v^x:
f^(x+1)=i^(x+1) so f=i....
its an identity so how cn u singl out Vi???